2022
DOI: 10.1007/s10597-022-01035-4
|View full text |Cite
|
Sign up to set email alerts
|

“Sometimes that Takes You Going the Extra Mile”: The Role of Providers’ Self-efficacy in Refugee Mental Health Services

Abstract: To achieve equity for refugee patients in mental health care settings, patient-centered, trauma-informed, and cultural humility practices have gained recognition; however, the use of these practices is not well defined. The implementation process of these practices may require providers’ increased self-efficacy, motivation, and cultural intelligence (CQ). Overall, this study aims to understand training needs of health care providers to be able to provide refugee patients with culturally meaningful, patient-cen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 37 publications
(51 reference statements)
0
1
0
Order By: Relevance
“…129 Having a solid belief in one's own capabilities is the most prominent factor that encourages people to confront the challenges of intercultural experiences, as it gives them the confidence to tackle various problems. 130 Yalim et al 131 found that healthcare professionals must have a high level of self-efficacy and cultural understanding when providing mental health services for refugees, which enables them to communicate effectively with patients from diverse cultural backgrounds. In the school setting, both multicultural and monocultural students with stronger self-efficacy were more successful in adapting to different cultures because people with higher self-efficacy are usually more capable of managing their emotions and dealing with challenges in an intercultural setting.…”
Section: Academic Self-efficacy and Cultural Intelligencementioning
confidence: 99%
“…129 Having a solid belief in one's own capabilities is the most prominent factor that encourages people to confront the challenges of intercultural experiences, as it gives them the confidence to tackle various problems. 130 Yalim et al 131 found that healthcare professionals must have a high level of self-efficacy and cultural understanding when providing mental health services for refugees, which enables them to communicate effectively with patients from diverse cultural backgrounds. In the school setting, both multicultural and monocultural students with stronger self-efficacy were more successful in adapting to different cultures because people with higher self-efficacy are usually more capable of managing their emotions and dealing with challenges in an intercultural setting.…”
Section: Academic Self-efficacy and Cultural Intelligencementioning
confidence: 99%